Quantitative standardization of pharmacologically active components from antiplasmodial plant Solanum nudum Dunal (wild and in vitro) (2022)
Solanum nudum Dunal (Solanaceae) is most commonly known and used by the population of the colombian Pacific coast as an antimalarial treatment. This article study into optimization and quantitative analysis of compounds steroidal over time of development of this species when grown in vitro and wild. A new steroidal compound named SN6 was elucidated by NMR and a new method of quantification of seven steroidal compounds (Diosgenone DONA and six steroids SNs) using HPLCDAD-MS in extracts of cultures in vitro and wild was investigated. Biology activity of extracts was found to a range of antiplasmodial activity in FCB2 and NF-54 with inhibitory concentration (IC50) between (17.04 -100 μg/mL) and cytotoxicity in U-937 of CC50 (7.18 -104.7 μg/mL). This method creates the basis for the detection of seven sterols antiplasmodial present in extracts from S. nudum plant as a quality parameter in the control and expression of phytochemicals.